Extensive mandibular multiloculation in a patient with Nevoid Basal Cell Carcinoma Syndrome: Case Report - Jesuino, Rômulo Dias; Ballesteros, Guillermo Enrique Blanco; Silva, Cláudia Jordão; Cardoso, Sérgio Vitorino; Barbosa, Gabriella Lopes de Rezende; Henriques, João César Guimarães (Journal of Oral Diagnosis, 2023)
Gorlin Goltz Syndrome, or Nevoid Basal Cell Carcinoma Syndrome, is an autosomal dominant genetic disease characterized especially by the manifestation of basal cell carcinomas in the skin and keratocysts in the jaws. Additionally, patients may present with several other manifestations, such as bifid ribs, hypertelorism and calcification of the falx cerebri. The diagnosis has physicians and dentists as protagonists in the investigation and involves a good anamnesis associated with a detailed physical examination, imaging, anatomical and histopathological exams and, if possible, the identification of the PTCH1 gene, which covers approximately 85% of patients. The present study aims to present an up-to-date integrative literary review of the Gorlin Goltz Syndrome, highlighting the care and management of the case of a syndromic patient treated at a stomatology clinic, carrying a series of major and minor findings of the disease.